Low-cost ultrahigh-strength maraging steel suitable for additive manufacturing

By adjusting the chemical composition and heat treatment process of martensite aging steel, low-cost ultra-high strength martensite aging steel is prepared, which solves the problem of high cost in additive manufacturing and achieves both high strength and good plasticity.

CN119859779APending Publication Date: 2025-04-22NANJING UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311364512.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing martensite aging steel in the field of additive manufacturing contains expensive Co elements, which leads to high production costs for parts and is not suitable for mass production.

Method used

By adjusting the chemical composition of martensite aging steel, reducing the content of Ni and Mo, increasing the content of Cr, Mn and Ti, and carrying out solid solution of 700-850℃ and aging treatment of 400-500℃, low-cost ultra-high strength martensite aging steel was prepared.

Benefits of technology

It achieves the maintenance or improvement of the strength and plasticity of steel while reducing costs. It is suitable for additive manufacturing. The additive block has no cracking and good density. The tensile experimental results show that the tensile strength is not less than 1.6Gpa, and the elongation after break is not less than 8.0%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859779A_ABST
    Figure CN119859779A_ABST
Patent Text Reader

Abstract

The invention discloses low-cost ultrahigh-strength maraging steel suitable for additive manufacturing. The low-cost ultrahigh-strength maraging steel comprises the following chemical components in percentage by mass: less than or equal to 0.03% of C, 13.0-15.0% of Ni, 2.5-3.5% of Mo, 2.5-3.5% of Cr, 1.3-2.5% of Mn, 0.50-0.80% of Ti, 0.05-0.15% of Al, less than or equal to 0.10% of Si, less than or equal to 0.010% of S, less than or equal to 0.010% of P and the balance of Fe. Alloy components are optimized to obtain low-cost ultrahigh-strength maraging steel components suitable for additive manufacturing, after the maraging steel components are made into wires or powder, a formed part obtained through additive manufacturing is subjected to solid solution for 1 h at the temperature of 700-850 DEG C and aging for 6 h at the temperature of 400-500 DEG C, the tensile strength of the formed part is not lower than 1.6 Gpa, and the percentage elongation after fracture is not lower than 8.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal additive manufacturing, and in particular to a low-cost ultra-high-strength steel suitable for additive manufacturing. Background Art

[0002] Additive manufacturing technology, commonly known as 3D printing technology, is an emerging manufacturing technology that has evolved from the integration of digital processing, laser technology, materials science and other disciplines. Compared with traditional subtractive manufacturing technology, additive manufacturing shapes materials according to three-dimensional model data by stacking them layer by layer. The advantage is that it does not require molds and is not limited by the shape of parts; it reduces the steps of mechanical processing and improves material utilization and processing speed. Additive manufacturing technology is currently a hot topic for scientific researchers. It meets the needs of modern manufacturing for product preparation and has broad application prospects.

[0003] Maraging steel is an advanced ultra-low carbon or even carbon-free high-strength steel with ultra-high strength and good toughness. Since maraging steel is mainly used in aerospace, high-end tooling and other fields, these fields often require parts to have highly complex spatial structures and excellent mechanical properties, and the number of parts required is relatively small, so it is suitable for production using additive manufacturing technology.

[0004] At present, maraging steels used in the field of additive manufacturing, such as 18Ni300, contain relatively expensive Co elements in their composition, which leads to high costs when producing parts and is not conducive to mass production. The applicant has found through a large number of experimental studies that when the Co element in maraging steel 18Ni300 is removed, Ni is reduced to 13.0-15.0%, Mo is reduced to 2.50-3.50%, Cr is added at 2.50-3.50%, and Mn is added at 1.30-2.50%, after solution treatment at 700-850℃ for 1h and aging treatment at 400-500℃ for 6h, the tensile strength is not less than 1.6Gpa and the elongation after fracture is not less than 8.0%. Summary of the invention

[0005] In order to solve the above-mentioned problems of maraging steel, the present invention aims to provide a low-cost ultra-high strength maraging steel suitable for additive manufacturing and a preparation method thereof. Compared with the 18Ni300 maraging steel commonly used in additive manufacturing, the low-cost ultra-high strength maraging steel has a lower content of the more expensive Ni and Co elements in its composition, which reduces the cost while making the additively manufactured parts have both excellent strength and good plasticity. Experiments show that this type of steel has good formability and machinability.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is calculated by mass percentage: C: ≤0.03%, Ni: 13.0-15.0%, Mo: 2.5-3.5%, Cr: 2.5-3.5%, Mn: 1.3-2.5%, Ti: 0.50-0.80%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0008] The method for preparing the low-cost ultra-high-strength maraging steel suitable for additive manufacturing specifically comprises the following steps:

[0009] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0010] (2) The cast rods are subjected to multiple forging, rolling, and drawing processes to form wires, and ultra-high-strength steel blocks are prepared by using the CMT (cold metal transition) additive manufacturing method.

[0011] (3) heat treating the ultra-high strength steel block to obtain ultra-high strength maraging steel.

[0012] Preferably, a 0.8-1.6 mm wire is used to prepare an ultra-high strength steel block using a CMT additive manufacturing method, wherein the wire feeding speed is set to 3-5 m / min, the welding speed is 20-40 cm / min, the welding current is 180-240 A, and the ultra-high strength steel block is additively manufactured on a substrate, with each layer of weld bead on the block being perpendicular to the next layer of weld bead.

[0013] Preferably, the ultra-high strength steel block is subjected to solution treatment at 700-850°C for 1 hour and aging treatment at 400-500°C for 6 hours to obtain ultra-high strength maraging steel.

[0014] The present invention also provides another method for preparing low-cost ultra-high strength maraging steel by additive manufacturing, which specifically comprises the following steps:

[0015] (1) Preparing the required materials according to the designed composition, placing the prepared raw materials into an induction melting furnace for melting, and preparing powders by a vacuum argon aerosol method;

[0016] (2) Screening the prepared powder to obtain powder with a particle size of 15 to 53 μm, and preparing an ultra-high strength steel block by an additive manufacturing method using SLM (selective laser melting technology);

[0017] (3) heat treating the ultra-high strength steel block to obtain ultra-high strength maraging steel.

[0018] Preferably, powder with a diameter of 15 to 53 μm is used for selective laser melting to prepare blocks, wherein the laser power is set to 180 to 300 W, island scanning with a spot diameter of 130 μm is selected, the scanning speed is 600 to 1800 mm / s, the scanning interval is 60 to 80 μm, the powder layer thickness is 30 μm, and the ultra-high strength steel block is additively manufactured on a substrate.

[0019] Preferably, the ultra-high strength steel block is subjected to solution treatment at 700-850°C for 1 hour and aging treatment at 400-500°C for 6 hours to obtain ultra-high strength maraging steel.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention designs a low-cost ultra-high-strength maraging steel suitable for additive manufacturing. A large number of experimental results show that the alloy system has good formability when used for additive manufacturing, the additive block has no cracking, and the density is good. The tensile test results show that the tensile strength of the tensile specimen obtained by additive manufacturing after solid solution aging treatment is not less than 1.6Gpa, and the elongation after fracture is not less than 8.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the additive block formed in Example 1 of the present invention.

[0023] Figure 2 This is the metallographic structure of the block sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below with reference to specific examples. The examples are merely descriptions of the implementation modes of the present invention and do not limit the scope of the present invention in any way.

[0025] The present invention provides a low-cost ultra-high-strength maraging steel suitable for additive manufacturing, wherein the chemical composition of the steel is as follows by mass percentage: C: ≤0.03%, Ni: 13.0-15.0%, Mo: 2.5-3.5%, Cr: 2.5-3.5%, Mn: 1.3-2.5%, Ti: 0.50-0.80%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0026] The above ingredients are designed based on the following:

[0027] Function of C element: Carbon is the most commonly used strengthening element in steel. It strengthens steel by forming solid solution and carbide precipitation. In maraging steel, due to solubility, the content of carbon solid solution in martensite structure is relatively small. As the carbon content continues to increase, the excess carbon will precipitate in the form of carbides, which will rapidly reduce the plasticity of the steel. Therefore, in maraging steel, the carbon content is generally controlled to ≤0.03%.

[0028] Function of Ni element: Nickel can improve the strength of steel while maintaining good plasticity and toughness. At the same time, nickel can improve the processability and weldability of steel, and improve the corrosion resistance of steel. It is not only resistant to acid and alkali, but also resistant to atmospheric corrosion. Nickel is the main component element of the strengthening precipitation phase in martensitic aging steel. Ni, Al and Ti can form Ni3Al and Ni3Ti dispersed in the martensitic matrix, thereby improving the strength of martensitic aging steel. A large number of experimental results show that the appropriate nickel content of the low-cost ultra-high strength martensitic aging steel suitable for the present invention is 13.0-15.0%.

[0029] Mo element effect: Mo has a solid solution strengthening effect on ferrite and can improve the stability of carbides. Molybdenum can refine the grains of steel, improve hardenability and heat resistance, and have good mechanical properties and creep resistance at high temperatures. Molybdenum can prevent the precipitation phase from precipitating along the austenite grain boundaries and avoid intergranular fracture. In addition, molybdenum can improve the corrosion resistance of steel in reducing media and prevent pitting and crevice corrosion. However, molybdenum will cause low-alloy steel to have a tendency to graphitize, and too much molybdenum will cause an increase in residual austenite. Therefore, the appropriate molybdenum content of the low-cost ultra-high strength maraging steel suitable for the present invention is 2.50-3.50%.

[0030] Cr element function: Chromium can improve the strength and hardness of steel, and can form a thin oxide film on the surface of steel to improve the oxidation resistance and corrosion resistance of steel. However, chromium will reduce the stability of austenite and increase the ferrite content in steel. At the same time, chromium will reduce the Ms point, and the element content should not be too high. Therefore, the appropriate chromium content of the low-cost ultra-high strength maraging steel suitable for the present invention is 2.50-3.50%.

[0031] Effect of Mn: Manganese plays a role of solid solution strengthening in steel, has strong hardenability, can increase the stability of austenite, but will reduce the toughness of maraging steel. Therefore, the suitable manganese content of the low-cost ultra-high strength maraging steel suitable for the present invention is 1.30-2.50%.

[0032] Effect of Ti element: Titanium can improve the strength and hardness of maraging steel and promote the formation of retained austenite. In addition, titanium can refine austenite grains and improve alloy strength and toughness. However, when the titanium content in steel is greater than 1.20%, the plasticity and toughness of the steel will deteriorate rapidly. Therefore, the suitable titanium content of the low-cost ultra-high strength maraging steel suitable for the present invention is 0.50-0.80%.

[0033] Function of Al element: Aluminum is usually used as a deoxidizing and nitrogen fixing agent in the production of steel. Aluminum can improve the strength of maraging steel, inhibit the precipitation of carbides, and improve the oxidation resistance of steel. However, aluminum promotes the formation of ferrite, and too much aluminum will affect the cutting performance of steel. Therefore, the suitable aluminum content of the low-cost ultra-high strength maraging steel suitable for the present invention is 0.05-0.15%.

[0034] It should be pointed out that the effects of the above elements refer to the effects of the single element added. The interaction of several elements added at the same time is still a subject that needs to be studied in additive manufacturing, and the synergistic effect of the elements can only be determined through experimental research. The final low-cost ultra-high strength maraging steel obtained after solution aging treatment has a tensile strength of not less than 1.6Gpa and an elongation after fracture of not less than 8.0%.

[0035] The method for preparing the low-cost ultra-high-strength maraging steel suitable for additive manufacturing specifically comprises the following steps:

[0036] A maraging steel block is prepared by using a CMT (cold metal transfer arc welding) additive manufacturing method using a 0.8-1.6 mm wire, the wire feeding speed is set to 3-5 m / min, the welding speed is 20-40 cm / min, the welding current is 180-240 A, and the maraging steel block sample is additively manufactured on a substrate, and each layer of the block is perpendicular to the next layer of the weld.

[0037] The present invention also provides another method for preparing low-cost ultra-high strength maraging steel by additive manufacturing, which specifically comprises the following steps:

[0038] Powder with a diameter of 15 to 53 μm is used for selective laser melting to prepare a block, the laser power is set to 180 to 300 W, island scanning with a spot diameter of 130 μm is selected, the scanning speed is 600 to 1800 mm / s, the scanning interval is 60 to 80 μm, the powder layer thickness is 30 μm, and the maraging steel block sample is additively manufactured on a substrate.

[0039] Due to the differences in the composition of each element in different embodiments, in order to ensure the formability of the additive manufacturing block, the printing parameters of each embodiment also vary within a certain range. After solution treatment at 700-850℃ for 1h and aging at 400-500℃ for 6h, the mechanical properties of the maraging steel are as follows: the tensile strength is not less than 1.6Gpa, and the elongation after fracture is not less than 8.0%.

[0040] Embodiment 1:

[0041] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.08%, Mo: 3.13%, Cr: 3.41%, Mn: 1.39%, Ti: 0.54%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0042] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0043] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the block sample size was 10×10×10 cm. Each layer of the block weld was perpendicular to the next layer of weld. The manufactured sample was cut into two types of samples parallel to the substrate and perpendicular to the substrate, such as Figure 1 shown.

[0044] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. The tensile strength, yield strength and elongation at break in the direction parallel to the substrate were 1202MPa, 532MPa and 10.0%, respectively; the tensile strength, yield strength and elongation at break in the direction perpendicular to the substrate were 1163MPa, 495MPa and 11.5%, respectively.

[0045] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0046] The metallographic specimens were made and the microstructure of the specimens was observed. It was found that the structure of the additive body was lath martensite and austenite. The specimens had no obvious defects such as pores and cracks and had good density. Figure 2 shown.

[0047] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standards and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1663MPa, 1523MPa and 8.0%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1602MPa, 1512MPa and 9.5%, respectively.

[0048] Embodiment 2:

[0049] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.08%, Mo: 3.13%, Cr: 3.41%, Mn: 1.39%, Ti: 0.54%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0050] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0051] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0052] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 700°C for 1 hour and an aging treatment at 425°C for 6 hours to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0053] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0054] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 700°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1623MPa, 1493MPa and 9.6%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1613MPa, 1467MPa and 10.5%, respectively.

[0055] Embodiment 3:

[0056] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.08%, Mo: 3.13%, Cr: 3.41%, Mn: 1.39%, Ti: 0.54%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0057] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0058] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0059] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 850° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0060] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0061] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 850°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1635MPa, 1473MPa and 9.3%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1602MPa, 1437MPa and 9.8%, respectively.

[0062] Embodiment 4:

[0063] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.08%, Mo: 3.13%, Cr: 3.41%, Mn: 1.39%, Ti: 0.54%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0064] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0065] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0066] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 400° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0067] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0068] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 400°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1617MPa, 1481MPa and 9.5%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1605MPa, 1457MPa and 10.2%, respectively.

[0069] Embodiment 5:

[0070] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.08%, Mo: 3.13%, Cr: 3.41%, Mn: 1.39%, Ti: 0.54%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0071] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0072] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0073] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 500° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0074] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0075] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 500°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1621MPa, 1497MPa and 9.6%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1611MPa, 1463MPa and 10.1%, respectively.

[0076] Embodiment 6:

[0077] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.27%, Mo: 3.26%, Cr: 3.19%, Mn: 1.95%, Ti: 0.77%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0078] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0079] (2) The low-cost ultra-high strength maraging steel component was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 35 cm / min, the welding current was 210 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0080] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0081] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0082] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1634MPa, 1528MPa and 8.9%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1621MPa, 1516MPa and 9.7%, respectively.

[0083] Embodiment 7:

[0084] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 13.11%, Mo: 3.49%, Cr: 3.26%, Mn: 1.74%, Ti: 0.58%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0085] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0086] (2) The low-cost ultra-high strength maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 3.5 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0087] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0088] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0089] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1634MPa, 1512MPa and 9.2%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1607MPa, 1510MPa and 9.6%, respectively.

[0090] Embodiment 8:

[0091] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.94%, Mo: 2.67%, Cr: 2.51%, Mn: 2.76%, Ti: 0.81%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0092] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0093] (2) The low-cost ultra-high strength maraging steel component was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 25 cm / min, the welding current was 200 A, and the additive manufacturing size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0094] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 850° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0095] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0096] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 850°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1694MPa, 1551MPa and 8.4%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1646MPa, 1492MPa and 8.9%, respectively.

[0097] Embodiment 9:

[0098] A low-cost ultra-high strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.39%, Mo: 2.71%, Cr: 2.83%, Mn: 2.13%, Ti: 0.62%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0099] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0100] (2) The low-cost ultra-high strength maraging steel component was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 190 A, and the additive manufacturing size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0101] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 850° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0102] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0103] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standards and tensile performance tests were carried out. After solution treatment at 850°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1643MPa, 1534MPa and 8.6%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1617MPa, 1527MPa and 9.4%, respectively.

[0104] Embodiment 10:

[0105] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 13.57%, Mo: 2.89%, Cr: 3.32%, Mn: 1.64%, Ti: 0.69%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0106] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0107] (2) The prepared powder was sieved, and the low-cost ultra-high strength maraging steel component was made into a powder of 15 to 53 μm. The low-cost ultra-high strength maraging steel block was prepared using SLM technology. The laser power was set to 240 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1200 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0108] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0109] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0110] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standards and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1682MPa, 1515MPa and 8.3%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1654MPa, 1486MPa and 9.6%, respectively.

[0111] Embodiment 11:

[0112] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 13.94%, Mo: 2.98%, Cr: 3.16%, Mn: 2.42%, Ti: 0.73%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0113] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0114] (2) The prepared powder was sieved, and the low-cost ultra-high strength maraging steel component was made into a powder of 15 to 53 μm. The low-cost ultra-high strength maraging steel block was prepared using SLM technology. The laser power was set to 220 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1000 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0115] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0116] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0117] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1639MPa, 1545MPa and 9.1%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1631MPa, 1529MPa and 10.0%, respectively.

[0118] Embodiment 12:

[0119] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 13.26%, Mo: 3.47%, Cr: 2.65%, Mn: 1.98%, Ti: 0.59%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0120] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0121] (2) The prepared powder was sieved, and the low-cost ultra-high strength maraging steel component was made into a powder of 15 to 53 μm. The low-cost ultra-high strength maraging steel block was prepared using SLM technology. The laser power was set to 280 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 800 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0122] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 800° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0123] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0124] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 800°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1667MPa, 1553MPa and 8.7%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1636MPa, 1536MPa and 9.5%, respectively.

[0125] Embodiment 13:

[0126] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 14.18%, Mo: 2.64%, Cr: 3.37%, Mn: 1.86%, Ti: 0.67%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0127] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0128] (2) The prepared powder was sieved, and the low-cost ultra-high strength maraging steel component was made into a powder of 15 to 53 μm. The low-cost ultra-high strength maraging steel block was prepared using SLM technology. The laser power was set to 260 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1400 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0129] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 850° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0130] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0131] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 850°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1675MPa, 1571MPa and 8.5%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1652MPa, 1568MPa and 9.6%, respectively.

[0132] Embodiment 14:

[0133] A low-cost ultra-high-strength maraging steel suitable for additive manufacturing, the chemical composition of which is as follows by mass percentage: C: ≤0.03%, Ni: 13.71%, Mo: 2.58%, Cr: 3.39%, Mn: 2.04%, Ti: 0.74%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0134] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0135] (2) The prepared powder was sieved, and the low-cost ultra-high strength maraging steel component was made into a powder of 15 to 53 μm. The low-cost ultra-high strength maraging steel block was prepared using SLM technology. The laser power was set to 180 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1600 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0136] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 850° C. for 1 h and an aging treatment at 425° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0137] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0138] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 850°C for 1h and aging at 425°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1686MPa, 1591MPa and 8.3%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1635MPa, 1529MPa and 9.5%, respectively.

[0139] Comparative Example 1:

[0140] 18Ni300 maraging steel, its chemical composition by mass percentage is: C: ≤0.03%, Ni: 18.39%, Mo: 5.05%, Co: 9.58%, Ti: 0.61%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0141] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, melting the prepared raw materials in an induction melting furnace, and casting them into solid bars;

[0142] (2) The maraging steel composition was made into a 1.6 mm wire, and the obtained wire was additively manufactured using CMT technology. The wire feeding speed was set to 4 m / min, the welding speed was 30 cm / min, the welding current was 200 A, and the additive manufacturing size was a block sample of 10×10×10 cm. Each layer of weld bead in the block was perpendicular to the next layer of weld bead. The manufactured samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0143] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 820° C. for 1 h and an aging treatment at 490° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0144] Metallographic samples were made and the microstructure of the samples was observed. It was found that the microstructure of the additive body was lath martensite and austenite. The samples had no obvious defects such as pores and cracks and had good density.

[0145] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 820°C for 1h and aging at 490°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1915MPa, 1778MPa and 3.8%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1852MPa, 1739MPa and 4.6%, respectively.

[0146] Comparative Example 2:

[0147] 18Ni300 maraging steel, its chemical composition by mass percentage is: C: ≤0.03%, Ni: 17.89%, Mo: 5.52%, Co: 9.03%, Ti: 0.76%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0148] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0149] (2) The prepared powder was sieved, and the maraging steel component was made into a powder of 15 to 53 μm. Low-cost ultra-high strength maraging steel blocks were prepared using SLM technology. The laser power was set to 240 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1200 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0150] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 820° C. for 1 h and an aging treatment at 490° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0151] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0152] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standard and tensile performance tests were carried out. After solution treatment at 820°C for 1h and aging at 490°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 2027MPa, 1976MPa, and 1.5%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 2007MPa, 1945MPa, and 3.0%, respectively.

[0153] Comparative Example 3:

[0154] 18Ni300 maraging steel, its chemical composition by mass percentage is: C: ≤0.03%, Ni: 17.89%, Mo: 5.52%, Co: 9.03%, Ti: 0.76%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0155] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0156] (2) The prepared powder was sieved, and the maraging steel component was made into a powder of 15 to 53 μm. Low-cost ultra-high strength maraging steel blocks were prepared using SLM technology. The laser power was set to 240 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1200 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0157] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 780° C. for 1 h and an aging treatment at 490° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0158] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0159] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standards and tensile performance tests were carried out. After solution treatment at 780°C for 1h and aging at 490°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1944MPa, 1852MPa and 4.0%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1918MPa, 1792MPa and 5.0%, respectively.

[0160] Comparative Example 4:

[0161] 18Ni300 maraging steel, its chemical composition by mass percentage is: C: ≤0.03%, Ni: 17.89%, Mo: 5.52%, Co: 9.03%, Ti: 0.76%, Al: 0.05-0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

[0162] (1) Preparing the materials required for ultra-high strength steel according to the designed composition, placing the prepared raw materials into an induction melting furnace for smelting, and preparing powder by a vacuum argon aerosol method;

[0163] (2) The prepared powder was sieved, and the maraging steel component was made into a powder of 15 to 53 μm. Low-cost ultra-high strength maraging steel blocks were prepared using SLM technology. The laser power was set to 240 W, and the island scanning with a spot diameter of 130 μm was selected. The scanning speed was 1200 mm / s, the scanning interval was 70 μm, and the block size of the additive was 10×10×10 cm. The prepared samples were cut into two types of samples, one parallel to the substrate and the other perpendicular to the substrate.

[0164] (3) The low-cost ultra-high strength maraging steel block is subjected to a solution treatment at 860° C. for 1 h and an aging treatment at 490° C. for 6 h to obtain a precipitate phase to improve the strength of the ultra-high strength steel block.

[0165] Metallographic samples were made and the microstructure of the samples was observed. It was found that the structure of the additive body was lath martensite and austenite; the samples had few pores, no obvious cracks, and high density.

[0166] In accordance with the national standard for tensile tests, the additive body was made into tensile test specimens that meet the national standards and tensile performance tests were carried out. After solution treatment at 860°C for 1h and aging at 490°C for 6h, the tensile strength, yield strength and elongation at break parallel to the substrate were 1926MPa, 1837MPa and 4.7%, respectively; the tensile strength, yield strength and elongation at break perpendicular to the substrate were 1893MPa, 1750MPa and 5.5%, respectively.

[0167] Table 1 Specific Example Composition Table (wt.%)

[0168]

[0169]

[0170] In addition to the components given in Table 1, the remaining elements are C≤0.03%, Al 0.05-0.15%, Si≤0.10%, S≤0.010%, P≤0.010%, and the balance is Fe.

[0171] Table 2 Actual measured values ​​of various performances

[0172]

[0173]

[0174] Note: lateral σ b , σ 0.2 , δ are tensile strength, yield strength and elongation parallel to the substrate direction, longitudinal σ b , σ 0.2 , δ are the tensile strength, yield strength and elongation at break perpendicular to the substrate, and the unit of strength is MPa.

[0175] The low-cost ultra-high-strength maraging steel prepared by the present invention is not limited to the above-mentioned additive manufacturing technologies, and the embodiments do not constitute a limitation on the protection scope of the present invention. Any equivalent replacement or change based on the technical solution and the inventive concept of the present invention shall fall within the protection scope of the patent of the present invention.

Claims

1. A low-cost ultra-high strength maraging steel suitable for additive manufacturing, characterized in that: Its chemical composition by mass percentage is: C: ≤0.03%, Ni: 13.0~15.0%, Mo: 2.5~3.5%, Cr: 2.5~3.5%, Mn: 1.3~2.5%, Ti: 0.50~0.80%, Al: 0.05~0.15%, Si: ≤0.10%, S: ≤0.010%, P: ≤0.010%, and the balance is Fe.

2. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 1, characterized in that: Ultra-high-strength steel blocks are prepared by additive manufacturing technology, and then ultra-high-strength maraging steel is obtained through heat treatment.

3. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 2, characterized in that: Ultra-high strength maraging steel is obtained by solution treatment at 700-850℃ for 1h and aging treatment at 400-500℃ for 6h.

4. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 2, characterized in that: The wire is prepared according to its chemical composition ratio, and the ultra-high strength steel block is prepared by the additive manufacturing method using CMT.

5. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 4, characterized in that: 0.8~1.6mm wire is prepared according to its chemical composition ratio, and the ultra-high strength steel block is prepared using the CMT additive manufacturing method, wherein the wire feeding speed is set to 3~5m / min, the welding speed is set to 20~40cm / min, the welding current is set to 180~240A, and each layer of weld of the block is perpendicular to the next layer of weld.

6. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 2, characterized in that: Powders are prepared according to their chemical composition ratio, and ultra-high-strength steel blocks are prepared by using the SLM additive manufacturing method.

7. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to claim 6, characterized in that: Powders of 15-53 μm were prepared according to the chemical composition ratio, wherein the laser power was set to 180-300 W, the island scanning with a spot diameter of 130 μm was selected, the scanning speed was 600-1800 mm / s, the scanning interval was 60-80 μm, and the powder layer thickness was 30 μm.

8. The low-cost ultra-high strength maraging steel suitable for additive manufacturing according to any one of claims 1 to 7, characterized in that: The tensile strength of the aging steel is not less than 1.6 GPa, and the elongation after fracture is not less than 8.0%.

9. A method for preparing low-cost ultra-high strength maraging steel suitable for additive manufacturing, characterized in that: The steps include: According to the chemical composition ratio of the ultra-high strength maraging steel as claimed in claim 1, wire or powder is prepared, and an ultra-high strength steel block is prepared by an additive manufacturing method; The ultra-high strength steel block is heat treated to obtain ultra-high strength maraging steel.

10. The method according to claim 9, characterized in that The ultra-high strength steel is subjected to solution treatment at 700-850° C. for 1 hour and aging treatment at 400-500° C. for 6 hours to obtain ultra-high strength maraging steel.

Citation Information

Cited By

  • Low-cost corrosion-resistant ultrahigh-toughness steel for laser additive manufacturing and heat treatment method of low-cost corrosion-resistant ultrahigh-toughness steel

    CN121065600A

  • Low-cost corrosion-resistant ultra-high strength and toughness steel for laser additive manufacturing and heat treatment method thereof

    CN121065600B

  • Ultrahigh-strength steel powder for additive manufacturing, ultrahigh-strength steel, preparation method and application

    CN121514485A